Development of alternate cropping pattern Mustard -Boro –T.aman against fallow - Boro- T. Aman in Kushtia region - Rahman, MS; Islam, MT (Bangladesh Journal of Agricultural Research, 2019)
The experiment was conducted at Kushtia Sadar, Bheramara and Gangni Multi Location Testing (MLT) sites under On-Farm Research Division (OFRD), BARI, Kushtia (AEZ 11) during the last week of July to second week of May for three consecutive years (2013- 14, 2014-15 and 2015-16) to develop alternate cropping pattern (Mustard-Boro -T.Aman) and to compare its productivity and profitability against farmer’s existing cropping pattern (Fallow - Boro-T.Aman). The mustard (var: BARI Sarisha-14), Boro rice (var: BRRI dhan28) and T.Aman (var: Binadhan-7) were used in alternate cropping pattern, while BRRI dhan28 for Boro rice and BRRI dhan39/Sorna for T.Aman rice were used in the existing cropping pattern. Findings revealed that the mean crop duration of alternate cropping pattern ranged 269-287 days by inclusion of mustard. Rice equvalent yield of alternate cropping pattern was 13.98 t ha-1 year-1 which was 34% higher than that of existing pattern (10.47 t ha-1 year-1). Land use efficiency (76.44%) and labour employment (441 mandays ha-1 year-1) of alternate cropping pattern were 33 and 26%, higher, respectively than those of existing cropping pattern. The mean gross return (Tk. 2,53,960 ha-1) and gross margin (Tk. 99,513/ha) of alternate cropping pattern were 29 and 32%, respectively higher compared to those of existing cropping pattern (Gross return: Tk. 1,97,346 ha-1 and Gross margin: Tk. 75,340 ha-1) due to inclusion of high yielding variety of mustard. Therefore, farmers in Kushtia region of Bangladesh could follow alternate cropping pattern in their high and medium high land where lands remain fallow after harvesting of T. Aman rice for higher crop productivity and profitability. Bangladesh J. Agril. Res. 44(1): 69-78, March 2019